THE DYNAMICS OF THE MEANING OF THE TERM AL AMR IN ITS DESIGNATION AND APPLICATION IN NASH AND ITS LEGAL IMPLICATIONS - Rahul, Kaisar; Fatmawati; Rauf Muhammad Amin, Abd. (Institut Agama Islam Negeri Bone, 2025)
This study analyzes the semantic dynamics of lafaz al-amr (imperative form) in the context of its designation and application in Islamic scriptural texts (nash) and its implications for legal determination. Despite numerous studies on al-amr, in-depth research on meaning variations based on linguistic, historical, and socio-cultural contexts, as well as their legal implications, remains limited. The research problems are: how does the semantic dynamics of al-amr function in various contexts of nash, and what are the legal implications of different interpretations of al-amr. This research employs a qualitative method with a normative-juridical approach through textual analysis of Quranic verses and hadiths containing the shighat al-amr (imperative formula). The findings indicate that the meaning of al-amr is contextual and variable, depending on the form of shighat, qarinah (contextual indicators), and socio-historical context. Its legal implications encompass obligatory (wajib), recommended (sunnah), permissible (mubah), or advisory (irsyad), which require comprehensive interpretation to maintain the relevance and justice of Islamic law application in contemporary contexts.